Perlindungan Hukum Terhadap Pelaku Usaha Penanaman Modal Usaha Industri Beralkohol - Ulfah Fauziah; Suratman Suratman; Isdiyana Kusuma Ayu (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2022)
The legal vacuum occurred before the enactment of a replacement regulation regarding new investment in the alcoholic industry, until the ratification of Presidential Regulation Number 49 of 2021, especially on the issue of the validity of regulations and legal protection for investment business actors, for this reason it is necessary to analyze how legal protection is for business actors and legality of investment regulations in the alcoholic industry after the amendment of Presidential Regulation Number 10 of 2021 through normative juridical research, legal approaches and concepts. Based on the research results, the legal protection of business actors is based on Law Number 8 of 1999 concerning Consumer Protection. Legality of Investment is legal, based on Law Number 25 of 2007 concerning Investment, but new investment in the alcoholic industry is not reopened based on Presidential Regulation Number 49 of 2021 concerning Amendments to Presidential Regulation Number 10 of 2021 concerning Business Fields Capital investment.